2013
DOI: 10.1371/journal.pone.0055147
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Level of the BCL11B Protein Is Associated with Adult T-Cell Leukemia/Lymphoma

Abstract: BackgroundAdult T-cell leukemia/lymphoma (ATLL) develops in a small proportion of human T-cell leukemia virus type I (HTLV-I)-infected individuals. However, the mechanism by which HTLV-I causes ATLL has not been fully elucidated. To provide fundamental insights into the multistep process of leukemogenesis, we have mapped the chromosomal abnormalities in 50 ATLL cases to identify potential key regulators of ATLL.ResultsThe analysis of breakpoints in one ATLL case with the translocations t(14;17)(q32;q22-23) res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
(39 reference statements)
1
10
0
1
Order By: Relevance
“…Kurosawa et al . 18 showed that the BCL11B expression levels in HTLV-1-infected cells were downregulated relative to those in HTLV-1-infected cells. To elucidate the mechanism responsible for this, we measured the expression of BCL11B in various human T-cell lines, including HTLV-1-transformed and ATL-derived cell lines by performing western blot analyses and RT-PCR assays.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kurosawa et al . 18 showed that the BCL11B expression levels in HTLV-1-infected cells were downregulated relative to those in HTLV-1-infected cells. To elucidate the mechanism responsible for this, we measured the expression of BCL11B in various human T-cell lines, including HTLV-1-transformed and ATL-derived cell lines by performing western blot analyses and RT-PCR assays.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic alterations of BCL11B, such as by chromosomal rearrangements, have been identified in several T-ALL patients. 17 Intriguingly, HTLV-1-infected T-cells, including ATL cells, have been reported to have reduced BCL11B protein expression, 18 but the mechanism remains to be elucidated. In the present study, we show that the HTLV-1 oncoprotein Tax is sufficient to downregulate BCL11B expression in T-cells.…”
mentioning
confidence: 99%
“…Further clarification is needed as reduced Bcl11b expression has been associated both with promotion and apoptosis of T cell leukemia and lymphoma [72, 73]. Although Bcl11b +/− mice are known to be more susceptible to radiation-induced thymic lymphomas, may undergo modest T cell developmental arrest, and have elevated levels of proliferative βcatenin despite reduced preTCR signaling [48, 74], in the absence of other mutations a single wild-type allele appears sufficient to prevent cell transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Bcl11b has been observed as a target of the mir-17 cluster (Lewis et al, 2003; Zeller et al, 2003) as well as miR-93 and let-7 in T cells (Kurosawa et al, 2013). Given the accumulating data of the importance of Bcl11b in critical brain regions such as hippocampus, the expression of microRNAs targeting Bcl11b in the hippocampus is a fertile area for further study.…”
Section: Neuronal Expression Of Bcl11b In Development and Adulthoodmentioning
confidence: 99%